PELATIHAN PEMBUATAN HAND SANITIZER DARI TANAMAN SEKITAR RUMAH PADA REMAJA DI DESA - Nurbaity Situmorang; Siti Nurlani; Saiful Amir; Dini Novita Sari; Juhardi Sembiring; Siti Khairani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Klambir village is one of the villages located in Hamparan Perak sub-district, Deli Serdang Regency. Deli Serdang Regency itself is one of the regions that has the largest Covid cases in North Sumatra besides Medan City and Simalungun Regency. So that the socialization regarding the making of hand sanitizers in one of them in Deli Serdang Regency is very important in order to disseminate the community to maintain health in order to break the chain of transmission of COVID 19. The expected output targets from this activity are: Pepople in Klambir village, especially the teenager can understand and able to practice the making of hand sanitizers, the community is more familiar with some natural home ingredients that can be used as the basic ingredients for natural hand sanitizers, people are more concerned with maintaining their own hygiene in order to break the chain of transmission of COVID 19 and hope that good cooperation can be established between UNUSU, the village government and the community Villages in order to support the Government's program to break the chain of transmission of COVID-19 in Indonesia.